2018
DOI: 10.1186/s12885-018-4720-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes acquisition of aggressive phenotypes in human malignant mesothelioma

Abstract: BackgroundHypoxia is a hallmark of the solid tumor microenvironment and is associated with poor outcomes in cancer patients. The present study was performed to investigate mechanisms underlying the hypoxia-induced phenotypic changes using human malignant mesothelioma (HMM) cells.MethodsHypoxic conditions were achieved by incubating HMM cells in the air chamber. The effect of hypoxia on phenotype changes in HMM cells was investigated by performing in vitro clonogenicity, drug resistance, migration, and invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Various studies have explored the role of EMT in MM: Casarsa et al [22] showed the importance of EMT markers in MM prognosis, and others [22,23] evaluated the prognostic value of EMT markers in MM. Kim et al [24] proposed HIF-1α as a mediator of MM transformation via EMT event.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have explored the role of EMT in MM: Casarsa et al [22] showed the importance of EMT markers in MM prognosis, and others [22,23] evaluated the prognostic value of EMT markers in MM. Kim et al [24] proposed HIF-1α as a mediator of MM transformation via EMT event.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies showed the expression of pluripotency genes and proteins in mesothelioma cell lines, but not in human mesothelium or mesothelioma. This includes OCT4 protein expression [ 27 ], POU5F1 , NANOG and SOX2 gene expression in cell lines [ 28 , 29 ] or cancer-initiating cells [ 30 ]. Conversely, it has been also shown that POU5F1 , NANOG and SOX2 are not expressed in mesothelioma cell lines [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compact aggregation of tumor cells and reduced blood flow can result in tumor tissue hypoxia. Low oxygen levels at the tumor site subsequently facilitate cancer cell stemness and multidrug transporter expression, thus resulting in CDDP resistance [66,67,68,69,70]. Preclinical studies have indicated that antiangiogenic drugs, such as bevacizumab, can improve the flow of tumor vessels (vascular normalization) and the delivery function of coadministrated chemotherapy drugs [83].…”
Section: Emerging Perspectives On Cddp Resistance From the Tmementioning
confidence: 99%